Neighborhood Policy, Cross-border Cooperation and the Re-bordering of the Italy–Tunisia Frontier. Issue 3 (3rd July 2017) - Celata, Filippo; Coletti, Raffaella; Stocchiero, Andrea
ABSTRACT: This article focuses on the contents and outcomes of the cross-border cooperation program between Italy and Tunisia in light of a review of the limits of the European Neighborhood Policy and of its impact on the construction of the EU external frontiers. The transfer of the CBC policy model to this and similar cases, it is argued, produces ambivalent results due to various asymmetries and the lack of a proper multi-level governance of trans-border relations. Some suggestions are proposed about how a renewed approach may increase the political relevance of the program, support the democratic transition in Tunisia and contribute to a rethinking of Euro-Mediterranean policies.